Amsterdamse Ateliers. - Bakker, Ernst; Brunsmann, Peter; Niemeyer, L.J.; Rijmers, Jos (Amsterdam : Stichting Woon- en Werkruimten voor Kunstenaars, 1995)
Warffemius, Jan Carel ; Beeldsnijder, Frans ; Blits, Mieke ; Bottema, Nel ; Constant ; Diederen, Jef ; van Duin, Harm ; Duiven, Femmie ; van Duynhoven, Martin ; Günermengi, Arhan ; Hooykaas, Madelon ; Kletter, Barbara ; Kneulman, Carel ; Landsaat, Hans ; Lehmann, Bernd ; Lo-A-Nior, Guillaume ; Schipholt, Herman Lutje ; Matubaka, Tsietsi ; Ruyter, Mirjam ; Schoonheyt, Mary ; Sleutel, Stef Jurriën ; Tap, Wim ; Valenteijn, Wiep ; Wagt, George Van der ; Wiecherink, Dries
Nederlands
boek